2021
DOI: 10.1016/j.dib.2021.107310
|View full text |Cite
|
Sign up to set email alerts
|

Data on effect of Tempeh Fermentation on patients with type II diabetes

Abstract: Type II diabetes (T2D) arises through insulin resistance and a progressive decrease in insulin secretion, which may be partly related to pancreatic beta-cell function decline, obesity, and eventual hyperglycemia [1] . The first line for managing hyperglycemia in patients with T2D includes lifestyle modifications and metformin monotherapy. However, many patients still showed poor glycemic control due to progressive deterioration during the course of T2D [2 , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Tempeh also reduces insulin resistance, HbA1c, and serum glucose levels in streptozotocin combined with high-fat diet-induced T2D rats (Huang et al, 2018). Additionally, our previous results suggested that consuming 2 g of tempeh daily for a period of 3 months attenuated HbA1C and triglyceride levels in participants (Su et al, 2021). These findings suggest that tempeh ameliorates hyperglycemia, hyperlipidemia, and hyperinsulinemia.…”
Section: Accepted Manuscriptmentioning
confidence: 73%
See 2 more Smart Citations
“…Tempeh also reduces insulin resistance, HbA1c, and serum glucose levels in streptozotocin combined with high-fat diet-induced T2D rats (Huang et al, 2018). Additionally, our previous results suggested that consuming 2 g of tempeh daily for a period of 3 months attenuated HbA1C and triglyceride levels in participants (Su et al, 2021). These findings suggest that tempeh ameliorates hyperglycemia, hyperlipidemia, and hyperinsulinemia.…”
Section: Accepted Manuscriptmentioning
confidence: 73%
“…The previous study indicated that the nematodes of C. elegans share several fundamental physiological and stress response processes with their homologues in most human genes (60%-80%), including multiple signal transduction pathways (Kaletta and Hengartner, 2006b). Additionally, our previous clinical study also suggested that tempeh attenuated HbA1C and triglyceride levels in participants (Su et al, 2021). Therefore,…”
Section: Accepted Manuscriptmentioning
confidence: 87%
See 1 more Smart Citation
“…In the United States, the nutritional content per 84 g of commercial Tempeh includes 14.5 ± 2.4 g protein, 7.0 ± 4.6 g fiber, 0.6 ± 0.7 g saturated fat, 0.8 ± 1.3 g sugar, 14.2 ± 6.3 g carbohydrate, 152.5 ± 15.9 cal energy, 64.4 ± 22.3 mg calcium, 153.8 ± 151.2 mg potassium, 0.8 ± 1.1 g monounsaturated fatty acids, and 1.2 ± 1.6 g polyunsaturated fatty acids, all being free of cholesterol as well as trans fatty acids (Ahnan‐Winarno et al, 2021 ). Our previous clinical study results suggested that 2‐g Tempeh daily for a period of 3 months attenuated HbA1c and triglyceride levels in participants (Su et al, 2021 ). One animal study suggested that a high‐grade protein and fiber diet could remodel the gut microbiota, resulting in improved glycemic control and ameliorated diabetes (Ni et al, 2022 ).…”
Section: Resultsmentioning
confidence: 94%
“…A prospective open‐label trial showed that tempeh consumption improves glycemic control and triglyceride levels 123 .…”
Section: Potential Beneficial Effect Of Fermented Soybean Foods On Di...mentioning
confidence: 99%